3D sketching in immersive environments: Shape from disordered ribbon strokes - Bonneau, Georges-Pierre; Hahmann, Stefanie (Computers & graphics, 2024)
Immersive environments with head mounted displays (HMD) and hand-held controllers, either in Virtual or Augmented Reality (VR/AR), offer new possibilities for the creation of artistic 3D content. Some of them are exploited by mid-air drawing applications: the user’s hand trajectory generates a set of stylized curves or ribbons in space, giving the impression of painting or drawing in 3D. We propose a method to extend this approach to the sketching of surfaces with a VR controller. The idea is to favor shape exploration, offering a tool, where the user creates a surface just by painting ribbons. These ribbons are not constrained to form patch boundaries for example or to completely cover the shape. They can be very sparse, disordered, overlap or not, intersect or not. The shape is computed simultaneously, starting with the first piece of ribbon drawn by the user and continuing to evolve in real-time as long as the user continues sketching. Our method involves minimizing an energy function based on the projections of the ribbon strokes on a proxy surface by taking the controller’s orientations into account. The current implementation considers elevation surfaces. In addition to many examples, we evaluate the time performance of the dynamic shape modeling with respect to an increasing number of input ribbon strokes. Finally, we present images of an artistic creation that combines stylized curve drawings in VR with our surface sketching tool created by a professional artist. [Display omitted] •A novel VR sketch-based surface modeling tool is presented.•Ribbon strokes are drawn as if imitating the artist’s gesture while painting.•On-the-fly creation and updating of surfaces from disordered ribbon strokes.•Can process sparse, disordered, possibly overlapping ribbon strokes.•Interactive frame rates give immediate visual feedback on the sketching gestures.